The Genesis of the Establishment of the Institute of Legal Clinics in the World and in Ukraine - Mudrak, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
Was analysed of the historical establishment of the Institute of Legal Clinics in the world and the formation of a national network of legal clinics since the establishment of the first legal clinics in Ukraine, special attention has been paid to the functioning of legal clinics in law schools and law schools of Ukraine. Different authors’ approaches to understanding the concept of «legal clinic» are investigated.